Genus-Level Analysis of Gut Microbiota in Children with Autism Spectrum Disorder: A Mini Review - Mariya Levkova; Trifon Chervenkov; Rouzha Pancheva (MDPI AG, 2023)
Autism is a global health problem, probably due to a combination of genetic and environmental factors. There is emerging data that the gut microbiome of autistic children differs from the one of typically developing children and it is important to know which bacterial genera may be related to autism. We searched different databases using specific keywords and inclusion criteria and identified the top ten bacterial genera from the selected articles that were significantly different between the studied patients and control subjects studied. A total of 34 studies that met the inclusion criteria were identified. The genera Bacteroides, Bifidobacterium, Clostridium, Coprococcus, Faecalibacterium, Lachnospira, Prevotella, Ruminococcus, Streptococcus, and Blautia exhibited the most substantial data indicating that their fluctuations in the gastrointestinal tract could be linked to the etiology of autism. It is probable that autism symptoms are influenced by both increased levels of harmful bacteria and decreased levels of beneficial bacteria. Interestingly, these genera demonstrated varying patterns of increased or decreased levels across different articles. To validate and eliminate the sources of this fluctuation, further research is needed. Consequently, future investigations on the causes of autism should prioritize the examination of the bacterial genera discussed in this publication.